Global dataset on the presence of debris in nests of seabirds - Tavares, Davi Castro (Leibniz Centre for Tropical Marine Research, Bremen, Germany, 2020)
This dataset includes information on the presence of plastic debris in nests of 14 seabird species from different locations in the world. It also includes generated data for simulating bird species with high levels of prevalence of debris in nests. Methods related to data collection are described in Tavares et al. (2020). Confidence intervals and sample size for estimating the prevalence of plastic debris in seabird nests. Environmental Pollution. https://doi.org/10.1016/j.envpol.2020.114394